Ответ:
Объяснение:
-m(4-m)- (m-5)²=-4m+m²- (m² -10m+25)= - 4m + m² - m² +10m -25=6m -25
при m=- 5\6 6*(-5\6) -25= -5 - 25=-30
-20
надо вычислить и сократить дробь
-5/6(4-5/6)-(5/6-5)^2=-5/6×19/6-(-25/6)^2=-95/36-625/36=-20
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
Объяснение:
-m(4-m)- (m-5)²=-4m+m²- (m² -10m+25)= - 4m + m² - m² +10m -25=6m -25
при m=- 5\6 6*(-5\6) -25= -5 - 25=-30
Verified answer
Ответ:
-20
надо вычислить и сократить дробь
-5/6(4-5/6)-(5/6-5)^2=-5/6×19/6-(-25/6)^2=-95/36-625/36=-20